2008
DOI: 10.1002/humu.20634
|View full text |Cite
|
Sign up to set email alerts
|

Myocilinallele-specific glaucoma phenotype database

Abstract: Communicated by Daniel F. SchorderetGlaucoma, a complex heterogenous disease, is the leading cause for optic nerve-related blindness worldwide.Since 1997, when mutations in the myocilin (MYOC) gene were identified as causing juvenile onset as well as a proportion of primary open-angle glaucoma (POAG), more than 180 variants have been documented. Approximately one in 30 unselected patients with POAG have a disease-causing myocilin mutation and it has been shown that firm genotype-phenotype correlations exist. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 26 publications
1
113
2
4
Order By: Relevance
“…17,18 Interestingly the Myocilin gene, which has been unequivocally implicated in glaucoma and is not known to serve any physiological function, has been found to be highly expressed in the heart. 19,20 Using a clinic-based population, Tattersall et al 21 found that despite better IOP control, patients with OAG with a poor life expectancy lost more functional vision than severity-matched patients. In our study no association between disease severity and mortality cause was identified.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Interestingly the Myocilin gene, which has been unequivocally implicated in glaucoma and is not known to serve any physiological function, has been found to be highly expressed in the heart. 19,20 Using a clinic-based population, Tattersall et al 21 found that despite better IOP control, patients with OAG with a poor life expectancy lost more functional vision than severity-matched patients. In our study no association between disease severity and mortality cause was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in myocilin largely have their effect by dominant negative gain of function mechanism (Lam et al 2000). A total of 66 point mutations are listed in the HGMD database (www.hgmd.cf.ac.uk/ac/index.php) but a more comprehensive overview is provided in the myocilin mutation database (www.myocilin.com) (Hewitt et al 2008), where till date 74 disease causing mutations are listed. Myocilin mutations are generally associated with juvenile or early-adult form of POAG.…”
Section: Candidate Genes and Beyondmentioning
confidence: 99%
“…[10][11][12] In order to reduce the variability accounted for by disease-causing variants of different severity, we analysed individuals carrying only the most common MYOC variant (p.Gln368Ter) separately.…”
Section: Response To Treatmentmentioning
confidence: 99%
“…10 Since the discovery of the MYOC gene in 1997, over 80 disease-causing variants have been described, with the p.Gln368Ter variant the most common. 12 Although clear genotype-phenotype correlations exist, inter-and intrafamilial phenotypic variability is also well acknowledged. The p.Gln368Ter variant has a variable age-related penetrance with 50% of carriers diagnosed with glaucoma by 50 years of age.…”
Section: Introductionmentioning
confidence: 99%